A Survey of the Critically Endangered Vultures of Gashaka Gumti National Park, Nigeria - Aina, Stephen; Azugo, Somtochukwu; Joseph, Nelly; Gapkong, Elizabeth; Saidu, Yohanna; Kemabonta, Kehinde; Onoja, Joseph; Aminu-Kano, Muhtari (International Journal of Scientific Research in Biological Sciences, 2022)
The traditional significance attached to the vultures has made the bird of prey objects of inquests and persecutions by local actors with nonconformist disposition to wildlife conservation in Nigeria. With the ascendancy of wildlife persecutions, vultures are now rare across landscapes and previous information about vulture distribution remain largely altered, outdated and insignificant to guide precise conservation action. Our paper focuses on advancing baseline population statistics for the critically endangered vultures of the project location. From the eight (8) survey routes objectively allotted for data collection, Route 3 (Pompo 2A – Mayo-Yum) had the highest record of 21 individuals (30%) of Necrosyrtes monachus, while Route 1 (Gashaka –GF/Kwano - Filinga), had 13 individuals (92%) of the Gyps africanus recorded during the inventory. Across all the survey routes, 71 and 14 individuals of N. monachus and G. africanus, respectively, were sighted and enumerated. Thus, an overall unadjusted count of 85 individuals from two (2) species of the Critically Endangered (CE) vultures were encountered and recorded within Gashaka Gumti National Park and the support zone communities. The Park has, therefore, great potentials for the conservation of vultures considering its vast landmass of about 6,730 sq.km, the spread of pastoral settlements and diversity of local tribes. However, due to the low sampling intensity (< 1%) and several exploratory sightings of unnamed species of vultures by locals, complementary surveys are required to update existing records of vultures in the park. The park is significant to upholding vulture biodiversity at the habitat-level in Nigeria.